The Essence of Marriage Agreement as Protection in the Indonesian Marriage Law System - Akhmad Kamil Rizani; Muchimah Muchimah; Reza Noor Ihsan; Aris Sunandar Suradilaga (Jember: Sharia Faculty State Islamic University of Kiai Haji Achmad Siddiq Jember, 2024)
The purpose of this research is to know and understand the essence of a marriage agreement by a married couple in an effort to create a harmonious family. Indonesia, through Law Number 16 of 2019 concerning Amendments to Marriage Law Number 1 of 1974 concerning Marriage Article 29, regulates the time and object of marital agreements made by married couples. The research methodology used in this research is normative research (library research), using a statutory approach. The findings of this study show that a marriage agreement is an important legal instrument in providing protection and justice for married couples. Through this agreement, couples can formulate agreements regarding their respective rights and obligations, especially regarding property management and financial responsibilities, and create a more equal and fair relationship. In addition, the marriage agreement also acts as preventive and repressive legal protection, which can prevent conflicts and provide guidelines for settlement if disputes arise. Thus, a marriage agreement not only protects the rights of the spouses but also serves as a progressive and adaptive legal protection mechanism for changing times, providing an important guarantee of legal certainty for the parties to the marriage.